Parque Eco-Industrial: Uma discussão sobre o futuro dos distritos industriais brasileiros - Nascimento, Décio Estevão do; Casagrande Jr., Eloy Fassi; Moraes, Ligia Rosalinski; Ruthes, Sidarta (Revista Gestão da Produção Operações e Sistemas, 2006)
The objective of this article is to show the importance of the Eco-Industrial Parks as an instrumentfor sustainability and their competitive edge in the global economy. It is well-known the fact that the Brazilianindustrial districts need to be modernized regarding management and technology, so that they can be able tofollow worldwide trends of production. Otherwise, the industries may not be able to compete any longer. Inorder to perform this study, the exploration method was used to investigate and discuss the implantation of the“Eco-Industrial Park” model management in the Industrial District of Curitiba (CIC), by identifying someindustries that can form a closed and sustainable system, where partnership and enterprise cooperation can beestablished. In this study, it was also possible to identify some industries located at CIC which arecomplementary. They were able to develop partnerships and cooperation regarding exchange of by-productsand industrial residues to be used in their respective productive processes.Key words: Eco-Industrial Parks; Sustainable Development; Technological Prospection.